(untitled) (International Journal of Communication Systems and Network Technologies, 2024)
This article explores the evolutionary trajectory of voice assistants, surpassing traditional speech recognition to become versatile digital companions. With the integration of natural language understanding, multi-modal interfaces, and contextual awareness, these entities play pivotal roles in task automation, smart home integration, language translation, and accessibility, profoundly impacting user experience and daily life. As voice assistants continue to collaborate with third-party services, the article envisions an exciting future where these technologies redefine our interactions with digital assistants, shaping a new paradigm in technology evolution.